The Nuclear Pore Complex Function of Sec13 Protein Is Required for Cell Survival during Retinal Development - Niu, Xubo (American Society for Biochemistry and Molecular Biology, 2014)
Sec13 is a dual function protein, being a core component of both the COPII coat, which mediates protein trafficking from the endoplasmic reticulum to the Golgi apparatus, and the nuclear pore complex (NPC), which facilitates nucleo-cytoplasmic traffic. Here, we present a genetic model to differentiate the roles of these two functions of Sec13 in vivo. We report that sec13(sq198) mutant embryos develop small eyes that exhibit disrupted retinal lamination and that the mutant retina contains an excessive number of apoptotic cells. Surprisingly, we found that loss of COPII function by oligonucleotide-mediated gene knockdown of sec31a and sec31b or brefeldin A treatment did not disrupt retinal lamination, although it did result in digestive organ defects similar to those seen in sec13(sq198), suggesting that the digestive organ defects observed in sec13(sq198) are due to loss of COPII function, whereas the retinal lamination defects are due to loss of the NPC function. We showed that the retinal cells of sec13(sq198) failed to form proper nuclear pores, leading to a nuclear accumulation of total mRNA and abnormal activation of the p53-dependent apoptosis pathway, causing the retinal defect in sec13(sq198). Furthermore, we found that a mutant lacking Nup107, a key NPC-specific component, phenocopied the retinal lamination phenotype as observed in sec13(sq198). Our results demonstrate a requirement for the nuclear pore function of Sec13 in development of the retina and provide the first genetic evidence to differentiate the contributions of the NPC and the COPII functions of Sec13 during organogenesis.